PENGARUH TERPAAN TAYANGAN TUTORIAL REVIEW MAKE UP DI YOUTUBE TERHADAP MINAT BELI MAHASISWI ILMU KOMUNIKASI UNIVERSITAS RIAU - Martina Faulina; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Based on information gathered from detik.com YouTube is the second most used site in the world and according to data from Techinasia Youtube controls 43% of the world's video provider market. About 70% of Youtube users are related to music, but as time goes on, specifically for comedy-themed video content and tutorials, there are the most types of videos. The video tutorial is very diverse, according to Google Indonesia Head of Marketing, Veronica, one of the most watched videos is the make up tutorial video. The presence of a make up review video tutorial is very helpful for female students to appear with makeup especially for beginners. The high number of YouTube viewers and the large number of videos on tutorials and make up reviews uploaded on this video site have created an impact of buying interest as a result of exposure to various information. The purpose of this study was to determine the magnitude of the influence of exposure to tutorials on make up on YouTube tutorials on buying interest of Riau University Communication Studies students.The method used in this study is quantitative explanatory. While the theory used in this study is the Stimulus theory Response which contains an understanding of the impact or influence that occurs on the first party is a certain reaction of a particular stimulus. Data collection techniques using questionnaires both in the form of online forms of google docs or directly distributed. The population in this study were students of the University of Riau Communication Science class of 2012-2018, which numbered 502 people. The sampling technique used is random sampling. To find out how much influence between variables X and Y variables, the author uses Simple Linear Regression Analysis. Data processing is done using SPSS Windows version 20.The results of the study obtained a correlation coefficient of 0.469 while the significance of 0.000 <0.05, which means that there is an influence between exposure to tutorials on make up on Youtube tutorials on interest in buying University of Riau Communication Science students. The value of the Determination Coefficient (R²) is 0.220 or 22%. From the calculation of SPSS obtained above shows a value of 22% which states that it turns out that the exposure of Youtube media produces a weak influence on the interest in buying products contained in the video tutorial and review of make-up on Youtube.